2014
DOI: 10.1007/s00210-013-0955-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of paradoxical sleep deprivation on memory and oxidative stress

Abstract: Sleep has important functions for every organ in the body and sleep deprivation (SD) leads to disorders that cause irreparable damage. The aim of this study was to investigate behavioral and brain structural alterations in mice deprived of paradoxical sleep for 48 and 72 h. Working memory, aversive memory as well as levels of nitric oxide (NO) and thiobarbituric acid reactive substances (TBARS) in the hippocampus, body striatum, and prefrontal cortex were evaluated. Working memory was affected in the 48- and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 41 publications
2
28
0
1
Order By: Relevance
“…In contrast, previous studies using acute, but not chronic, sleep deprivation models showed increased TBARS or lipid peroxidation levels in the hippocampus, hypothalamus, thalamus, and cortex during acute SD [35,60,73]. …”
Section: Discussionmentioning
confidence: 61%
“…In contrast, previous studies using acute, but not chronic, sleep deprivation models showed increased TBARS or lipid peroxidation levels in the hippocampus, hypothalamus, thalamus, and cortex during acute SD [35,60,73]. …”
Section: Discussionmentioning
confidence: 61%
“…Elevated oxidative stress and insufficient antioxidant activities may result in liver cell injury. 2,15 Research has shown that there is an obvious circadian rhythm in the blood levels of melatonin released from pineal gland in vertebrates, with levels being higher at night and lower during the day. After synthesis, melatonin is released into the cerebrospinal fluid and blood immediately and then is distributed throughout the body in the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…1 Sleep is beneficial for every organ in the body, and sleep deprivation leads to disturbances that cause irreparable damage. 2 Reduction in sleep duration and sleep quality is progressively common in modern society and is likely linked to changes in the socio-economic environment and lifestyle. 3 The percentage of adults reported sleeping 6 hours or less increased by 5% -6% between 1985 and 2004 and with the advancement of age, sleeping hours progressively decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Durrant et al, testing auditory memory and using polysomnography and magnetic resonance in healthy volunteers, showed that weaker parahippocampal responses and stronger striatal responses occurred after sleep and this was predicted by the amount of slow wave sleep [8]. The latest findings provide further evidence consolidating the relationship of the striatum with sleep [15].…”
Section: Introductionmentioning
confidence: 94%